Analysis of the Relationship Between ADIPOR1 Variants and the Susceptibility of Chronic Metabolic Diseases in a Northeast Han Chinese Population - Wang, Fengling (Genet Test Mol Biomarkers, 2016)
Objective: Shared genetic variants in ADIPOR1 have been identified as closely related to coronary artery disease (CAD), type 2 diabetes (T2D), and T2D with CAD susceptibility, suggesting that these variants are strong candidates for the common soil hypothesis. Therefore, it is essential to analyze the relationship between ADIPOR1 variants and the susceptibility to CAD, T2D, and T2D with CAD in other populations. Materials and Methods: A case–control study was conducted which included three case cohorts [CAD (n = 316), T2D (n = 295), T2D with CAD (n = 302)], and a control cohort (n = 268) from a population in northeast China. Six ADIPOR1 single-nucleotide polymorphisms were genotyped by high-resolution melting and polymerase chain reaction–restriction fragment length polymorphism. Results: We confirmed that the shared variant, rs3737884*G, in ADIPOR1 is associated with CAD, T2D, and T2D with CAD (p-value range: 6.54E-6–1.82E-5, odds ratio [OR] range: 1.770–1.844) and that rs16850797*C is associated with T2D and T2D with CAD (p-value range: 0.001–0.001, OR range: 1.529–1.571). We also found that a novel shared variant, rs7514221*C, is associated with an increased susceptibility to CAD, T2D, and T2D with CAD (p-value range: 0.002–0.004, OR range: 1.194–2.382) in this population. Conclusions: ADPOR1 variants, rs3737884*G and rs7514221*C, may be shared risk factors associated with CAD, T2D, and T2D with CAD in a population of northeast China.